AI FOR ACCESSIBILITY IN DIGITAL MEDIA EDUCATION - Nath Babu, Murathoti Rajendra; Tungoe, Chumdemo; R.Vasanthan,; Pimple, Jagdish; Khandare, Kiran S.; Kalyani, Lohans Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Artificial Intelligence (AI) is transforming the digital media education field to be more accessible and inclusive to various learners. This paper discusses how AI based technologies can be implemented in digital media learning environment to help students with various types of physical, cognitive and sensory disabilities. The study is based on the principles of Universal Design of Learning (UDL) and the author is investigating the possibility of breaking down the barriers to content delivery and participation through the use of adaptive systems (-speech recognition, text to speech (TTS) and image recognition) that assist students with disabilities in their learning process. The study assesses the practical benefits and disadvantages of AI in educational accessibility using a mixed-method approach, which is a combination of classroom observation and comparative study of the AI (accessibility tools) and non-AI (accessibility tools). The results point to the role played by AI-driven applications in ensuring fair interaction whereby they can be used to create more personalized learning experience, enhance understanding and promote communication between students and teachers. This paper highlights that it is necessary to have open AI systems that consider fairness data protection and inclusivity in the design of education. The current study can be added to the current discussion about inclusive pedagogy in which responsible AI involves can improve access, as well as creativity and innovation in digital media education. The paper ends with policy suggestions on how policy makers, educators and technologists can come up with sustainable AI access models in future learning environments.